Improvement of the photorefractive response in bismuth and magnesium co-doped lithium niobate crystals via oxygen-vacancy modulation through controlled redox annealing - Wang, Shuolin; Wang, Weiwei; Zhang, Yuqi; Hu, Youyou; Zheng, Dahuai; Liu, Hongde; Kong, Yongfa (Frontiers in Physics, 2025)
In this study, bismuth (Bi) and magnesium (Mg) co-doped lithium niobate crystals (LN:Bi,Mg6.0) with a rapid photorefractive (PR) response were subjected to annealing treatments in oxygen and various argon atmospheres to modulate their oxidation-reduction states. The PR properties of LN:Bi,Mg6.0 crystals with different redox states, including saturation diffraction efficiency, response time, and sensitivity, were systematically characterized at laser wavelengths of 532 nm, 488 nm, and 442 nm. The results demonstrate that reduction treatment effectively shortens the response time and enhances the PR sensitivity of LN:Bi,Mg6.0 crystals. In particular, the crystal reduced in Ar atmosphere for 24 h exhibited a response time of 5.4 m at 442 nm, representing a 58% reduction compared to the as-grown crystal. O 1s X-ray photoelectron spectroscopy (XPS) revealed that changes in the redox state directly affect the concentration of oxygen vacancies (VO) in the crystal, thereby influencing its PR performance. As the VO increases, the PR response time initially decreases and then increases. In addition, based on the results of ultraviolet-visible (UV-Vis) absorption spectra and XPS, the defect structures of LN:Bi,Mg6.0 crystal with varying redox states were discussed.